(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
In the field of education, augmented reality (AR) has become a cutting-edge tool that offers immersive and interactive learning environments. The use of AR to improve reading comprehension while learning a language is examined in this article. Augmented Reality (AR) may produce captivating and contextualized reading experiences that enhance comprehension and retention by superimposing digital information on the real environment. This essay examines the theoretical underpinnings of augmented reality (AR), its advantages for the improvement of reading abilities, and useful implementation techniques for AR in language training. We show how AR may greatly enhance students’ reading comprehension and general language skills through in-depth examination and case studies.